Effects of STEM-Based Learning Using the FarmBot Educational Kit in Conjunction with Block-Based Programming on the Computational Thinking Skills of Primary School Students - จงไกรจักร, ภารวี; จงไกรจักร, วรรัตน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) evaluate the efficiency of a STEM-based instructional innovation integrating block-based programming through the FarmBot Educational Kit based on the E1/E2 efficiency criterion of 80/80; 2) compare the computational thinking skills of upper primary school students before and after learning through the innovation; and 3) examine students’ satisfaction with the learning activities. The study employed a one-group pretest–posttest experimental design. The sample consisted of 239 upper primary school students in the 2025 academic year from schools in Ratsada Subdistrict, Phuket Province, selected using stratified cluster sampling. Research instruments included STEM-based learning activities integrating block-based programming, a 25-item computational thinking test with content validity (IOC = 0.67–1.00) and reliability (Cronbach’s alpha = 0.89), and a five-point Likert-scale satisfaction questionnaire (Cronbach’s alpha = 0.91). Data were analyzed using mean, standard deviation, E1/E2 efficiency values, and paired samples t-test.           The results showed that the instructional innovation achieved an efficiency of 82.40/84.15, exceeding the standard criterion of 80/80. The posttest computational thinking score (x̄ = 18.65, S.D. = 1.95) was significantly higher than the pretest score (x̄ = 12.55, S.D. = 2.40) at the .001 level, with a large effect size (Cohen’s d = 1.11). Students demonstrated improvement across all dimensions of computational thinking, particularly in problem decomposition and pattern recognition. Overall satisfaction with the learning activities was at a high level (x̄ = 4.53, S.D. = 0.47). These findings indicate that the developed instructional innovation is effective in enhancing computational thinking skills among primary school students.